2011
DOI: 10.4067/s0717-95022011000200030
|View full text |Cite
|
Sign up to set email alerts
|

Study of Frequency of the Palmaris Longus Musclem in Chilean Subjects

Abstract: SUMMARY:The palmaris longus muscle (PLM) lies on the anterior region of the forearm, it is considered one of the most variable muscles in the human body, and its agenesis is the most frequent anatomic variation. The aim of this study was to evaluate the frequency of the PLM tendon in Chilean adults and also, to verify the agenesis symmetry according to sex. For this, we have analyzed the presence of the PLM tendon in 200 Chilean individuals, 114 female and 86 male. In this study, three different tests were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
3
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 15 publications
4
15
3
9
Order By: Relevance
“…The percentage of agenesis of the PL muscle in our case was greater than that reported by Kigera & Mukwaya in corpses in Southern Africa, similar to that reported by Thompson et al (2001) in Caucasian subjects in Northern Ireland (16 %), lower than that reported by Alves et al (2011) in Chilean adults, and lower than that reported by Ceyhan & Mavt in Indians. The differences in the incidences may be associated with the ethnic origin of the subjects.…”
Section: Discussioncontrasting
confidence: 54%
“…The percentage of agenesis of the PL muscle in our case was greater than that reported by Kigera & Mukwaya in corpses in Southern Africa, similar to that reported by Thompson et al (2001) in Caucasian subjects in Northern Ireland (16 %), lower than that reported by Alves et al (2011) in Chilean adults, and lower than that reported by Ceyhan & Mavt in Indians. The differences in the incidences may be associated with the ethnic origin of the subjects.…”
Section: Discussioncontrasting
confidence: 54%
“…Machado and DioDio 12 , Alves et al 13 and Thompson et al 14 have been the subject of studies on cadavers and also of clinical studies. 2,8 …”
Section: Discussionmentioning
confidence: 99%
“…In 1559, the absence of Palmaris longus muscle was described or the first time in Columbus' book, which was published soon after his death [15]. Several clinical trials an studies have been conducted since y many authors [16][17][18][19][20]. The absence of this muscle and tendon has also been reported in different ethnic groups, with wide variation [16][17][18][21][22][23].…”
Section: Males Femalesmentioning
confidence: 99%